KELANGSUNGAN HIDUP LARVA IKAN NILA GIFT (Oreochromis sp) YANG DIPELIHARA PADA SUHU DAN PADAT TEBAR BERBEDA - Rini Marlida; Mukhlisah; Ahmad Effendi (Chlorophyl, 2022)
This study aims to determine the effect of temperature and different stocking densities and their interaction on the survival rate of reared tilapia larvae. The method used in this study is an experimental method using 2 x 3 factorial completely randomized design (CRD) with 3 replications. The treatment applied in this study was a combination of different temperatures and stocking densities, where: A: The main treatment was temperature, including A1: 28oC, A2: 300C. B : The main treatments were stocking density, including: B1: stocking density of 15 fish/L, B2: stocking density of 20 fish/L, B3: stocking density of 25 fish/L. The results of survival studies on tilapia larvae in each treatment combination showed that treatment A1B1 had a survival of 97.33%, and treatment A1B2 97.00%, treatment A1B3 96.80%, followed by treatment A2B1 93.33%, treatment A2B2 92.00% and treatment A2B3 91.20%. However, from the ANOVA results, the treatment of the main factor A (temperature) and the main factor B (stocking density) as well as the interaction of the two factors A (temperature) and B (stocking density) did not have a significant effect